Exploring the LDS 821 dye as a potential NIR probe for the two photon imaging of amyloid fibrils. (1st October 2020) - Udayan, Sony; Sherin, D. R.; Vijaykumar, Samiyappan; Manojkumar, T. K.; Nampoori, V. P. N.; Thomas, Sheenu
Abstract : Nonlinear optical properties of near infrared dye LDS 821 incorporating lysozyme amyloid fibrils were studied at two wavelengths. The two photon absorption of the dye shows a large enhancement with lysozyme fibrils. Abstract : We report a commercially available benzothiazolium based dye LDS 821 (Styryl 9M) as a near infrared fluorescent probe for the detection of lysozyme amyloid fibrils. Change in the photophysical properties of the dye with respect to the change in viscosity of the environment is investigated. Increment in fluorescence lifetime and quantum yield with increment in viscosity proves the dye as a molecular rotor. The dye, upon binding with lysozyme fibrils, exhibits a red shift in the absorption spectrum with increased quantum yield. Strong fluorescence emission near the biological window as compared with Thioflavin T makes the LDS 821 dye a potential probe for imaging amyloid fibrils in vivo . Molecular docking studies were carried out to understand the mode of interaction between the dye and amyloid fibrils. Nonlinear optical properties of the dye upon incorporation with amyloid fibrils were explored, and they show a sizeable enhancement in two photon absorption with an increase in the concentration of amyloid fibrils. The findings suggest that the nonlinear optical absorption of the LDS 821 dye can be used as an alternative marker for amyloid fibrils.